The English Students' Critical Thinking Abilities with Learning Activities - Rei Christine Artauli; Sari Simbolon; Devi Agata Lubis; Rotua Theresia; Oriza Sativa Ellan (International Journal of Pedagogy, 2024)
The goal of this correlation study is to examine how students' critical thinking relates to learning activities. This study investigates "How do students think critically and learn activities in the EFL class?" This quantitative study focused on English students in the Department of Language Education, Faculty of Education, and Vocational Studies. Data were acquired from thirty respondents using two questionnaires: critical thinking and learning activities.Descriptive statistics (mean and standard deviation) were employed to examine student questionnaire results. This study found a substantial association between students' critical thinking and learning activities, as shown by M = (3.67) and M = (3.45). In general, English students' critical thinking during learning activities is classified as "current." In short, English students' critical thinking with learning activities indicates that they applied critical thinking abilities during the learning process. Future studies might look into how students think and behave in critical thinking and classroom learning activities.